Pengaruh Perubahan Harga Kebutuhan Pokok terhadap Pola Konsumsi Mahasiswa Perantau Program Studi Manajemen di Universitas Negeri Medan - Mica Siar Meiriza; Shintami Oktavia; Paula Florensia Munthe; Evelyn Electra; Intan Lutfiah Maharani (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the effect of changes in basic commodity prices on the consumption patterns of migrant students from the Management Study Program, Class of 2025, at Medan State University. This research employs a quantitative approach using a survey method and purposive sampling technique, involving 50 respondents. Data were collected through questionnaires and analyzed using validity, reliability, normality, and linearity tests, as well as simple linear regression analysis. The results indicate that the research instruments are valid and reliable, and the data are normally distributed with a linear relationship between variables. The regression analysis shows that changes in basic commodity prices have a positive and significant effect on the consumption patterns of migrant students, with a regression coefficient of 0.595 and a significance value of 0.000 (< 0.05). The coefficient of determination (R²) of 0.338 indicates that 33.8% of the variation in students’ consumption patterns can be explained by changes in basic commodity prices, while the remaining is influenced by other factors outside the scope of this study. These findings suggest that migrant students tend to adjust their consumption patterns in response to changes in basic commodity prices.